1999
DOI: 10.1007/s100720050028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and magnetic resonance imaging of carbon monoxide intoxication. A long-term follow-up study

Abstract: The clinical and neuroradiological outcome of carbon monoxide (CO) intoxication was evaluated prospectively in 30 patients over a follow-up period of 3 years. Among the patients studied, 22 had been acutely exposed to CO while 8 were chronically exposed. One month after CO poisoning, 12 of the 22 patients with acute intoxication showed magnetic resonance imaging (MRI) abnormalities: 6 also had neurological sequelae and 6 were asymptomatic. The remaining 10 patients showed neither MRI abnormalities nor neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
2
27
1
1
Order By: Relevance
“…[1][2][3][4][8][9][10][11][12][13][14][15] They include hindered executive function and slowed mental processing speed, which are often observed after frontal lobe damage, and altered visuospatial abilities, which are commonly observed after parietal lobe injury. 10 Central executive function involves corticocortical connectivity, 31 which depends mainly on complex WM networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][8][9][10][11][12][13][14][15] They include hindered executive function and slowed mental processing speed, which are often observed after frontal lobe damage, and altered visuospatial abilities, which are commonly observed after parietal lobe injury. 10 Central executive function involves corticocortical connectivity, 31 which depends mainly on complex WM networks.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 With conventional MR imaging, WM lesions are identified in 12%-37% of patients, but the findings are not related to the severity of intoxication. 10,11 Imaging appears to be relatively insensitive for assessing the clinical consequences of neurotoxicity in these patients.…”
mentioning
confidence: 99%
“…The largest study included 129 patients, and 33% of them had WM lesions on brain CT (Choi, Kim et al 1993). In patients with improvements of neurological deficits, resolution of WM changes have also been noted (Klostermann, Vieregge et al 1993;Matsushita, Takahashi et al 1996;Pavese, Napolitano et al 1999). Lesions of the WM area are believed to be associated with clinical outcomes (Miura, Mitomo et al 1985;Vieregge, Klostermann et al 1989;Choi, Kim et al 1993).…”
Section: Wm Lesionsmentioning
confidence: 94%
“…The study revealed no correlation between WM hyperintensities and carboxyhemoglobin level, or duration of CO exposure at any of the three scan times (Parkinson, Hopkins et al 2002). Hyperintensities in T2WI and fluid-attenuated inversion recovery (FLAIR) and hypointensities in T1WI often suggest WM demyelination or axonopathy (Chang, Han et al 1992;Pavese, Napolitano et al 1999;Parkinson, Hopkins et al 2002). From a pathological perspective, myelin damage is constant and can vary from discrete perivascular lesions to extensive periventricular demyelination and/or axonal destruction (Funata, Okeda et al 1982;Prockop and Chichkova 2007).…”
Section: Imaging Features Suggesting Wm Demyelination or Axonopathymentioning
confidence: 94%
See 1 more Smart Citation